Association of HLA-DQ5 and HLA-DR1 with sensitization to organic acid anhydrides. - Jones, MG; Nielsen, J; Welch, J; Harris, J; Welinder, H; Bensryd, I; Skerfving, S; Welsh, K; Venables, K; Taylor, A (2004)
BACKGROUND: Organic acid anhydrides are low molecular weight industrial chemicals, able to cause rhinoconjunctivitis and asthma associated with specific IgE against hapten-carrier protein conjugate. Only a proportion of exposed workers develop IgE-associated allergy to acid anhydrides. OBJECTIVE: We determined whether genetic susceptibility, in particular, HLA Class II alleles may be a risk factor. METHODS: We undertook HLA typing in 52 cases who had confirmed specific IgE and in 73 referents matched on site, age and duration of acid anhydride exposure identified in cross-sectional studies of workers exposed to hexahydrophthalic (HHPA), methylhexahydrophthalic (MHHPA) and methyltetrahydrophthalic (MTHPA) anhydrides. RESULTS: The linked alleles DQ5 (odds ratio [OR]=4.3; 95% confidence interval [95% CI]=1.7, 11) and DR1 (OR 3.0; 95% CI 1.2, 11) were more prevalent in cases than in referents. Within DQ5, DQB1(*)0501 was particularly frequent (OR 3.0; 95% CI 1.2, 7.4). CONCLUSION: DQB1(*)05 gene confers susceptibility to develop specific IgE antibodies against HHPA, MHHPA and a non-significant trend with MTHPA. DQB1(*)0501 is protective for other low molecular chemical sensitizers (isocyanates and plicatic acid) which may indicate varying affinities for the corresponding specific class II molecules.